1993
DOI: 10.1044/jshr.3604.842
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Patterns of Duration Discrimination

Abstract: The purpose of this study was to determine whether the auditory perceptual abilities of children are characterized by an age-related improvement in duration discrimination. Forty children, ages 4 to 10 years, and 10 adults served as subjects. Difference limens were obtained using a 350-msec broadband noise burst as the standard stimulus in a three-interval forcedchoice paradigm. Data were characterized by significant differences between the performances of the 4-, 6-, and 8-year-olds and those of the adults. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 22 publications
3
20
0
1
Order By: Relevance
“…Spectral abilities, as measured by spectral-ripple discrimination thresholds were statistically identical to those of adult CI users, but the child subjects were generally poor at the Schroeder-phase discrimination test and their scores were significantly worse than those of the adults. Previous studies demonstrated that temporal sensitivity takes longer to develop than frequency sensitivity, and normal-hearing children do not develop adult temporal processing ability until the age of 11 years [Wightman et al, 1989;Elfenbein et al, 1993;Buss et al, 1999]. In young normal-hearing listeners, peripheral temporal mechanisms may be adult-like, but the central auditory system may be less efficient in extracting temporal information [Plack and Moore, 1990].…”
Section: Discussionmentioning
confidence: 99%
“…Spectral abilities, as measured by spectral-ripple discrimination thresholds were statistically identical to those of adult CI users, but the child subjects were generally poor at the Schroeder-phase discrimination test and their scores were significantly worse than those of the adults. Previous studies demonstrated that temporal sensitivity takes longer to develop than frequency sensitivity, and normal-hearing children do not develop adult temporal processing ability until the age of 11 years [Wightman et al, 1989;Elfenbein et al, 1993;Buss et al, 1999]. In young normal-hearing listeners, peripheral temporal mechanisms may be adult-like, but the central auditory system may be less efficient in extracting temporal information [Plack and Moore, 1990].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is very difficult to assess whether children's ability to perceive consonant clusters is equivalent to that of adults. Although children's auditory perceptual systems are reported to undergo developmental changes ( Elfenbein, Small, & Davis, 1993), no studies to date have shown that children's cluster-perceiving mechanisms are deficient.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is not clear whether attention indeed drives the development of frequency discrimination or whether both attention and discrimination simply improve with age. As for the development of duration discrimination, to our knowledge this has been investigated in two published studies only (Elfenbein et al, 1993;Jensen & Neff, 1993), both showing development during the primary-school years.…”
Section: Introductionmentioning
confidence: 98%
“…Specifically, we are interested in the development of auditory frequency and duration discrimination, as previous reports indicate that adult-like discrimination performance is not attained prior to 10 years of age (Elfenbein, Small, & Davis, 1993;Moore, Cowan, Riley, Edmondson-Jones, & Ferguson, 2011) and that non-sensory factors are probably involved in this prolonged development Wightman & Allen, 1992).…”
Section: Introductionmentioning
confidence: 99%